IMMUNOPOSITIVE NEURONS MORPHOLOGY OF SUBSTANCE P IN THE HUMAN PARIETAL LOBULE CORTEX - Alexopoulos, Christos Georgios (Medicinski časopis, 2012)
ABSTRACT This investigation has been provided in order to find out is there any particular connection between the neuronal body shapes and their immunoreactivity. Substance P (SP) neuropeptide was examined. The largest somata were obtained among SP positive neurons: average diameters (± SD) were: longer diameter 44.93 ± 15.69 m, shorter diameter 18.16 ± 3.77 m. One-way analysis of variance (O-ANOVA) revealed the highly significant difference among longer axis of immunopositive neurons (p=0.002). Most of the detected neurons (25%) were localized in lamina II of the LPI cortex. The least populated layer was lamina I (less than 10% of all immunoreactive neurons). Key words: parietal cortex, neuropeptide, substance P, and laminar distribution